Resistance monitoring and mechanism in the fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) for chlorantraniliprole from Sichuan Province, China - Chen, Hui-Lin; Hasnain, Ali; Cheng, Qing-Hua; Xia, Li-Juan; Cai, Yu-Hao; Hu, Rong; Gong, Chang-Wei; Liu, Xue-Mei; Pu, Jian; Zhang, Lei; Wang, Xue-Gui (Frontiers in Physiology, 2023)
The fall armyworm (FAW), Spodoptera frugiperda (Noctuidae: Lepidoptera) is a wide-reaching notorious insect pest of important cereal crops, which has developed resistance to multiple classes of insecticides. It invaded to Sichuan Province of China in 2019. In this study, we performed resistance monitoring of insecticides for eleven field collected populations from Sichuan and all the populations were susceptible to emamectin benzoate and chlorpyrifos. The variations in resistant level to indoxacarb (resistance ratios, RR, 9.23- to 45.53-fold), spinetoram (RR, 4.32- to 18.05-fold) and chlorantraniliprole (RR, 2.02- to 10.39- fold) were observed among these populations. To investigate the resistance mechanism for chlorantraniliprole, synergism tests were performed and showed that piperonylbutoxide had a slight synergistic effect of chlorantraniliprole for the QJ-20 population (1.43-fold) in moderate resistance (RR, 10.39-fold) compared with treatment group without synergist. Furthermore, the expression scanning for resistance related genes showed that five P450 genes (CYP6AE43, CYP321A8, CYP305A1, CYP49A1 and CYP306A1) and ryanodine receptor gene (Ryr, chlorantraniliprole target) were over-expressed in QJ-20 population. These results indicated that the fall armyworm in Sichuan has exhibited diverse susceptibilities to several classes of insecticides and the overexpression of Ryr and several P450 genes may contribute to the development of resistance of S. frugiperda to chlorantraniliprole.